2022
DOI: 10.1101/2022.03.04.22271919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Neonatal Sepsis Admitted In Neonatal Intensive Care Unit At Public Hospitals Of Kaffa Zone, South West Ethiopia

Abstract: Background : Neonatal sepsis is a systemic inflammatory response syndrome in the presence of infection during the first 28 days of life. Globally every year about 4 million children die in the first 4 weeks of life, of which 99% of the deaths occur in low and middle income countries and the  most  common causes of neonatal  death  in  Ethiopia.  Identification of the determinants for neonatal sepsis and treatment of newborns with sepsis is not adequate in low income countries like Ethiopia especially in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Eight of them are case-control by design [9,11,[25][26][27][28][29][30] where the rest are cross-sectional [10,12,14,15,[31][32][33]. Five of the included studies are from Amhara region [9,10,14,25,33] four from Oromia [12,28,29,31], four from southern nation nationalities and peoples of the region (SNNPR) [26,27,30,32], one from Harari [15] , and one Tigray [11]. The total sample size of original studies included in this meta-analysis is 4,895.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight of them are case-control by design [9,11,[25][26][27][28][29][30] where the rest are cross-sectional [10,12,14,15,[31][32][33]. Five of the included studies are from Amhara region [9,10,14,25,33] four from Oromia [12,28,29,31], four from southern nation nationalities and peoples of the region (SNNPR) [26,27,30,32], one from Harari [15] , and one Tigray [11]. The total sample size of original studies included in this meta-analysis is 4,895.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The association between neonatal sepsis and prolonged PROM was examined based on the result of seven studies [9][10][11]27,28,31,32]. This meta-analysis indicated that a neonate born from pregnant mothers having prolonged PROM had 4.03 (OR: 4.03, 95: CI: 1.88-8.60) times higher odds of neonatal sepsis than their counterparts.…”
Section: Association Between Neonatal Sepsis and Prolonged Rupture Of...mentioning
confidence: 99%
See 1 more Smart Citation